2018
DOI: 10.3389/fendo.2018.00259
|View full text |Cite
|
Sign up to set email alerts
|

Deconvoluting the Biological Roles of Vitamin D-Binding Protein During Pregnancy: A Both Clinical and Theoretical Challenge

Abstract: The teleological purpose of an ongoing pregnancy is to fulfill its fundamental role of a successful, uncomplicated delivery, in conjunction with an optimal intrauterine environment for the developing fetus. Vitamin D metabolism is adapted to meet both these demands during pregnancy; first by stimulation of calcium absorption for adequate intrauterine bone mineral accrual of the fetus, and second, by enhancing systemic and local maternal tolerance to paternal and fetal alloantigens. Vitamin D-binding protein (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 73 publications
1
50
0
1
Order By: Relevance
“…Some aspects of vitamin D metabolism are of physiologic relevance in pregnancy [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Compared to non-pregnant women, there is a significant increase in 1,25(OH)2D concentrations, with a 2-fold increase in in the first trimester of pregnancy and a further rise to a 2- to 3-fold increase during the course of pregnancy and a rapid decline after delivery [ 35 ].…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Some aspects of vitamin D metabolism are of physiologic relevance in pregnancy [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Compared to non-pregnant women, there is a significant increase in 1,25(OH)2D concentrations, with a 2-fold increase in in the first trimester of pregnancy and a further rise to a 2- to 3-fold increase during the course of pregnancy and a rapid decline after delivery [ 35 ].…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
“…Several observational studies reported an increase of DBP during pregnancy with a peak of approximately 40–50% higher serum DBP concentrations compared to non-pregnant women at the beginning of the third trimester and a decline at term [ 38 ]. The liver is usually the major production site of DBP, but given that human placental trophoblasts express DBP on their cell surface, it has been speculated that the rise in DBP concentrations might be partially the result of the high turnover rate of trophoblasts.…”
Section: Vitamin D Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Вітамін D-зв'язуючий білок -це одна з ключових біомолекул, які оптимізують гомеостаз вітаміну D, а також сприяють імунному регулятору для здорової вагітності. У зв'язку з цим останні результати показують, що дисрегуляція рівноваги вітамін D-зв'язуючого білка може стати фактором ризику для плода, матері та новонародженого, включаючи прееклампсію, передчасні пологи та гестаційний діабет [18]. Згідно з результатами проведених досліджень, добавки кальцію, магнію та цинку мають значний вплив на профілактику ПЕ.…”
Section: акушерство та гінекологіяunclassified
“…At the Gc1 locus (rs7041) the G allele is associated with increased susceptibility to hepatitis C viral infection (71). Karras et al (72) has summarized a number of studies showing the impact of DBP and DBP polymorphisms on various outcomes of pregnancy. These studies demonstrate the recent interest in the impact of polymorphisms on DBP function, but it remains to be seen whether these initial results will be generalized across different populations.…”
Section: Biologic Functionmentioning
confidence: 99%